2023
DOI: 10.1002/smll.202305879
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of SBUs and Synergy of MOF Host–Guest in Single Crystalline State: Ingenious Strategies for Modulating Third‐Order NLO Signals

Yupei Sun,
Wenjuan Xu,
Feifan Lang
et al.

Abstract: Central metal exchange can innovatively open the cavity of metal‐organic frameworks (MOFs) by alternating the framework topology. Here, the single‐crystal‐to‐single‐crystal (SC‐SC) transformation is reported from a Co‐based MOF {[Co1.25(HL)0.5(Pz‐NH2)0.25(µ3‐O)0.25(µ2‐OH)0.25(H2O)]·0.125 Co·0.125 L·10.25H2O}n (Co‐MOF, L = 5,5'‐(1H‐2,3,5‐triazole‐1,4‐diyl)diisophthalic acid) into two novel MOF materials, {[Cu1.75L0.75(Pz‐NH2)0.125(µ3‐O)0.125(µ2‐OH)0.25(H2O)0.375]•3CH3CN}n (Cu‐MOF) and {[Zn1.75L0.625(Pz‐NH2)0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The β value of ZnCu-MOF-1 is calculated as 1.8 × 10 –8 m W –1 , while the β value of ZnCd-MOF-1 is calculated as 1.0 × 10 –8 m W –1 . The comparison of experimental results of different bimetal ratios shows that the introduction of more Cu 2+ and Cd 2+ can further adjust the electron structure, thus amplifying the nonlinear optical absorption effect. , …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The β value of ZnCu-MOF-1 is calculated as 1.8 × 10 –8 m W –1 , while the β value of ZnCd-MOF-1 is calculated as 1.0 × 10 –8 m W –1 . The comparison of experimental results of different bimetal ratios shows that the introduction of more Cu 2+ and Cd 2+ can further adjust the electron structure, thus amplifying the nonlinear optical absorption effect. , …”
Section: Resultsmentioning
confidence: 98%
“…shows that the introduction of more Cu 2+ and Cd 2+ can further adjust the electron structure, thus amplifying the nonlinear optical absorption effect. 25,28 In the closed aperture (CA) mode, Zn-MOF exhibits a valley followed by a peak, both equidistant from the focal point, indicating self-focusing behavior (n 2 > 0) (Figure 7b). It was demonstrated that Zn-MOF induces beam lateral beam distortion and manifests a self-focusing phenomenon under intense laser irradiation.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficient charge delocalization in the Ti 3 C 2 QD/V 2 C PMOF heterostructure imparts new linear optical spectroscopic features and expands the π-conjugate system, indicating a protruding NLO absorption, which can be observed in hybrid systems. 38,39,47,60,61 It holds great promise in nonlinear optics and other optoelectronic devices. 29,62,63 Overall, the systematic investigations of the energy alignment and electron transfer mechanisms in the Ti 3 C 2 QD/V 2 C PMOF heterostructure provide valuable insights into its optoelectronic properties, paving the way for the development of novel heterostructures with enhanced NLO functionalities.…”
Section: Resultsmentioning
confidence: 99%